2017
DOI: 10.24084/repqj15.285
|View full text |Cite
|
Sign up to set email alerts
|

Optimization Measures for Increased Immunity against High Frequency Disturbances and Reduced Emission in the Range of 2 kHz to 150 kHz Realized on Different LED Lamps

Abstract: In this paper, optimization measures to increase the immunity against high frequency (HF) disturbances by simultaneously reducing the impact on the grid through non sinusoidal input currents in the frequency range of 2 kHz to 150 kHz are presented. Two different light-emitting diode (LED) lamps as an example for typical electronic mass-market products are optimized. Currently, LED lamps are state of the art in the range of efficient lamps. But long-term experiences concerning their immunity against HF disturba… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
1
1

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 4 publications
0
2
0
Order By: Relevance
“…Especially these circuits with electrolytic capacitors are potentially affected by supraharmonic distortions due to its capacitive impedance behavior. [4], [7] Measurements with supraharmonic distortions of 2 V amplitude have shown that there is an up to doubled ripple current on the circuits' input capacitor [4]. The actual ripple current of the capacitor is highly dependent on the distortion's frequency and the distortion's amplitude.…”
Section: Impact Of Supraharmonic Distortions On Devicesmentioning
confidence: 99%
See 1 more Smart Citation
“…Especially these circuits with electrolytic capacitors are potentially affected by supraharmonic distortions due to its capacitive impedance behavior. [4], [7] Measurements with supraharmonic distortions of 2 V amplitude have shown that there is an up to doubled ripple current on the circuits' input capacitor [4]. The actual ripple current of the capacitor is highly dependent on the distortion's frequency and the distortion's amplitude.…”
Section: Impact Of Supraharmonic Distortions On Devicesmentioning
confidence: 99%
“…So, especially electronic mass-market equipment (LED lamps, USB power supplies etc.) and their built-in components like electrolytic capacitors for voltage smoothing are additionally stressed by these supraharmonic disturbances [4]. As a result, effects like malfunctions or impairments of the equipment have increasingly been noticed within the last few years [5], [6].…”
Section: Introductionmentioning
confidence: 99%